cDNA library construction from a small amount of RNA: adaptor-ligation approach for two-round cRNA amplification using T7 and SP6 RNA polymerases - Reiko Ohara; Reiko F. Kikuno; Hiroshi Kitamura; Osamu Ohara (BioTechniques)
In this study, we developed a method that allows cDNA library construction from a small amount of RNA without causing serious size bias in the resulting cDNA population. For this purpose, we adopted two-round cRNA amplification by T7 and SP6 RNA polymerases. The first-round cDNAs, flanked by the promoter sequences of T7 and SP6 RNA polymerases, were synthesized from 1 µg total RNA and then subjected to two rounds of cRNA amplification. Comparison of the sizes of the first-round and the second-round cRNAs indicated that the size-bias effect of the second-round cRNA synthesis was not serious. The resultant double-stranded cDNAs were cloned into a plasmid by in vitro λ phage recombination with an efficiency of 1.2 × 1011 colony-forming unit/microgram of starting total RNA. Characterization of the resultant cDNA library in terms of the insert size, clone redundancy, and integrity of 3′ ends of cDNAs indicated that the amplified library was comparable to a library constructed by a conventional method, although large cDNAs tend to be slightly truncated in the amplified library. This method enables the construction of a library from a small amount of RNA, and calculations suggest that the strategy would be efficient enough to use even a single cell as starting material.